1958
DOI: 10.1002/art.1780010604
|View full text |Cite
|
Sign up to set email alerts
|

Report of a three‐year study on the systemic and articular indexes in rheumatoid arthritis

Abstract: The author's methods of systemic and articular indexes have been an important advance in the field of evaluating disease activity and response to therapy in patients with rheumatoid arthritis. The present paper summarizes his experience with these methods and his present views on this controversial subject.Per su methodologia del indices systemic e articular, le autor ha promovite importantemente le evalutation del activitate marbide e del responsa therapeutic in patientes con arthritis rheumatoide. Le present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

1959
1959
1998
1998

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(42 citation statements)
references
References 10 publications
0
41
0
1
Order By: Relevance
“…Measures other than those recorded in Table 3 also showed significant improvement in patients on cyclophosphamide as compared to those on placebo during both Period I and Period 11, including Lansbury's articular index (P < 0.01) (20), number of joints showing a decrease of one or more ring size (P < O.Ol), and number of large joints showing a decrease in circumference of more than 1.0 cm (P < 0.01). These findings further substantiate the efficacy of cyclophosphamide in reducing the activity of arthritis in these patients.…”
Section: Measures Of Disease Activitymentioning
confidence: 84%
“…Measures other than those recorded in Table 3 also showed significant improvement in patients on cyclophosphamide as compared to those on placebo during both Period I and Period 11, including Lansbury's articular index (P < 0.01) (20), number of joints showing a decrease of one or more ring size (P < O.Ol), and number of large joints showing a decrease in circumference of more than 1.0 cm (P < 0.01). These findings further substantiate the efficacy of cyclophosphamide in reducing the activity of arthritis in these patients.…”
Section: Measures Of Disease Activitymentioning
confidence: 84%
“…All OA and RA patients were diagnosed and classified according to the criteria of the American Rheumatism Association (14,151. Total joint scores were computed according to the method of Lansbury (16). Disease duration was calculated from the date of the first appearance of symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Ninety patients received 100 mg capsules (M-group) and 89 were on 5 mg capsules as controls (C-group). At the onset a comparison of patients in the two groups revealed that they were balanced in most important respects, such as age, sex, body weight, in-or outpatients, duration of illness, each item of criteria for diagnosis of RA, stage, functional class, serum rheumatoid factor, coadministered drugs, rheumatoid activity index according to Lansbury (14) and severity of each item assessed by the Seven Day Variability Test of ARA (Table I).…”
Section: Patientsmentioning
confidence: 99%
“…The results disclosed that Lansbury's rheumatoid activity index of patients, assessed by duration of morning stiffness, grip strength, number of clinically active joints, and value of erythrocyte sedimentation rate (ESR) in 1 hour (14), reduced almost linearly within t h e first 4 m o n t h s of medication. Moreover, in 49 o f 168 patients (29%), positive serum rheumatoid factor became negative after treatment.…”
mentioning
confidence: 99%